Characteristics of Direct Shear and Particle Breakage of Pebble Gravel Materials. (4th August 2020) - Hong, Chenjie; Huang, Man; Zhang, Danyu; Shou, Pingshan; Zhu, Zhiyong
Abstract : Particle size is an important factor affecting the Thermal-Hydraulic-Mechanical (THM) coupling behavior of graveled rock mass, especially for the shear mechanical properties. In this study, three groups of the particle size range and nine particle grading samples are designed for a large-scale direct shear test. The relationships between shear stress and shear displacement, shear strength, stress ratio, shear strength parameters, and particle breakage of pebble gravel are analyzed. The influence of particle size range and grade on the strength and particle breakage of gravel material is discussed. Results show evident particle breakage in the process of direct shear, and the degree of fragmentation is controlled by the normal load and the particle size distribution of the sample. The shear strength of the sample is no longer applicable to Mohr-Coulomb strength theory because of particle breakage that is more in line with the power function relationship. Shear strength of pebble gravel material has scale effect, and a corresponding relationship model between friction coefficient f of material and characteristic particle size of the sample is proposed.